The effect of giving foot baths on lowering blood pressure in elderly people with hypertension - Lilis, Lilis Fitriani; Syanti Dewi Amir, Maya; Yulianti , Yeni (Jurnal Health Society, 2025)
ntroduction: Hypertension that occurs in the elderly can be overcome by giving foot baths. The purpose of this study was to determine the effect of foot soaking on lowering blood pressure in elderly people with hypertension. Methods: The type of this study is a quasi experiment with a non-evalent control group approach. The population was all elderly people with hypertension in Tipar Village, Tipar Health Center Working Area, Sukabumi City with a sample of 34 respondents divided into control and intervention groups of 17 people each using purposive sampling technique. Data were analyzed using paired sample t-test and independent sample t-test. Result: The paired sample t-test results showed no difference in systolic (p=0.234) and diastolic (p=0.055) blood pressure in the control group. While there is an effect of foot soak on reducing systolic blood pressure (p=0.000) and diastolic (p=0.000) in the intervention group. The results of the independent sample t-test test showed differences in systolic and diastolic blood pressure in the control and intervention groups (p=0.000). Conclusions: The conclusion in this study is that there is an effect of giving foot soaks on lowering blood pressure in elderly people with hypertension. And there are differences in blood pressure in the control group and intervention group. It is hoped that the results of this study can be used as a non-pharmacological treatment that can help reduce blood pressure in the elderly.